Kinetics of Chlorine Dioxide Oxidation of Benzidine in Wastewater - Cao, Xiangyu (Asian Journal of Chemistry, 2012)
Reaction kinetics of benzidine oxidation with ClO2 in the wastewater were investigated systematically by detecting concentrations of benzidine with HPLC at regular intervals. The results showed that the reaction was first-order with respect to both ClO2 and benzidine and the entire reaction was of second-order. Under condition of pH 6.5 and water temperature 298 K, the second-order reaction rate constant k was 5.721 × 10-4 L (mmol s)-1. The reaction activation energy was 51.1 kJ mol-1, revealing that the reaction could take place under usual water treatment conditions. The rate constants increased with the reaction pH increasing, then decreased. Hydrazobenzene, azobenzene and para-benzoquinone were detected by GC-MS as intermediates of the free benzidine-ClO2 reaction.